(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to investigation of specification of aspectual meaning of verbs with original Ukrainian prefix попо-. The features of the translation of such verbs in Russian are revealed.